Membuka Kekuatan Penyembuhan Seni: Kanvas Kolaboratif Online untuk Mempromosikan Pentingnya Seni & Komunitas dalam Kesejahteraan Mental - Gumulya, Shareen; Harditya, Arya (IMAGIONARY, 2023)
Declining mental health as well as mental disorders like severe depression and anxiety continues to be the main risk factor of suicide all around the world, including Indonesia. Depression in Indonesia is prevalent in young adults, with 6% of them suffering from moderate depression. This moderate depression, if not dealt with correctly, will lead to further disorders and even taking of one’s own life. Unfortunately, mental health care in the country is not as accessible as compared to other more developed countries. Complementary treatments such as making art, or art therapy, is an alternative that has been used to address the patient’s health requirements. Throughout the years, the use of art therapy has gradually increased and bore positive outcomes mainly among those suffering from depression disorders and anxiety. Therefore, this project explores effective approaches and practices of art therapy and combines it with new media technology, transforming a simple work of art into an interactive installation that also serves to promote the use of art in improving mental health. Keywords: Art Therapy, Depression, Interactive, Mental Health